THE ART OF ANCIENT PERU SEEN BY TRAVELERS OF THE 19TH CENTURY: WIENER, SQUIER AND MARCOY - Cabanillas, Virgilio Freddy (2004)
In this article we discuss the statements of three XIX century travelers: Paul Marcoy, Efrain G. Squier, and Charles Wiener, these travelers played a significant role in the process of discovery and revaluation of the autonomous Andean art. In their books, they described in detail artistic objects of several techniques, cultures, and periods. They also made high quality drawings of these objects and proposed audacious inter- pretations that had a significant influence due to the diffusion of their manuscripts. Marcoy was conuinced of the foreign origin of Andean cultures. In contrast, Squier advocated for the singularity of Andean art and eulogized its diferent manifestations. Meanwhile, Wiener criticized the patterns of human sculpture in the Andes under classic criteria, but remarked the quality of arquitectural buildings.